International Law and Chemical, Biological, Radio-Nuclear (CBRN) Events Towards an All-Hazards Approach - de Guttry, Andreas; Frulli, Micaela; Casolari, Federico; Poli, Ludovica (Brill, 2022)
This book explores the interplay between International Law and Chemical, Biological, Radio-Nuclear (CBRN) risks. An all-hazards approach is adopted to cover events of intentional, accidental and natural origin, and international obligations are presented according to the phases of the emergency management cycle, including prevention, preparedness, response and recovery.